Retention and survival rate of etanercept in psoriasis over 15 years and patient outcomes during the COVID-19 pandemic: The real-world experience of a single center - ONSUN, NAHIDE; GÜNEŞ, BEGÜM; GÜNEŞ, BEGÜM; ONSUN, Nahide; YABACI TAK, AYŞEGÜL; YABACI, AYŞEGÜL (My University, 2020)
There have been a number of investigations of the efficacy and safety of etanercept. This study was performed to obtain long-term drug survival data (ie, time to drug discontinuation) for etanercept, and the reasons for its discontinuation. The study population consisted of patients with psoriatic arthritis and psoriasis followed up by our clinic, registered in the Turkish Psoriasis Registry (PSR-TR) and treated with etanercept for at least 4 weeks between January 1, 2005, and January 31, 2020. The efficacy of etanercept was evaluated in terms of the Psoriasis Area and Severity Index (PASI) 75, PASI 90 and PASI 100 response rates at 12, 24, 36, and 48 weeks, and annually thereafter. The behaviors of the patients with respect to the use of etanercept, and the outcomes of those who continued to use it during the COVID-19 pandemic, were also investigated.
Keywords: COVID-19